Prophylactic Treatment with the C-Abl Inhibitor, Neurotinib, Diminishes Neuronal Damage and the Convulsive State in Pilocarpine-Induced Mice - Rojas-Montecinos, P; Lara-Suzarte, M (Elsevier B.V., 2024)
The molecular mechanisms underlying seizure generation remain elusive, yet they are crucial for developing effective treatments for epilepsy. The current study shows that inhibiting c-Abl tyrosine kinase prevents apoptosis, reduces dendritic spine loss, and maintains N-methyl-D-aspartate (NMDA) receptor subunit 2B (NR2B) phosphorylated in in vitro models of excitotoxicity. Pilocarpine-induced status epilepticus (SE) in mice promotes c-Abl phosphorylation, and disrupting c-Abl activity leads to fewer seizures, increases latency toward SE, and improved animal survival. Currently, clinically used c-Abl inhibitors are non-selective and have poor brain penetration. The allosteric c-Abl inhibitor, neurotinib, used here has favorable potency, selectivity, pharmacokinetics, and vastly improved brain penetration. Neurotinib-administered mice have fewer seizures and improved survival following pilocarpine-SE induction. Our findings reveal c-Abl kinase activation as a key factor in ictogenesis and highlight the impact of its inhibition in preventing the insurgence of epileptic-like seizures in rodents and humans. © 2024 The Authors